Attitude Towards Shopping Mall Purchasing Behavior - Manandhar, Raju Bhai (Management Dynamics, 2020)
Consume attitude is multidimensional and it has been one of the main concepts used to explain individual differences. This study aims to examine the relationship between overall attitude and shopping mall purchasing behavior and impact of advertising and purpose to visit on shopping mall purchasing behavior in Nepalese consumers. The present study is descriptive and analytical in nature. Structured questionnaire technique under survey approach was applied for collecting primary data with five point Likert scale questionnaire. The population of this study targeted the consumers of shopping malls in Kathmandu valley. The sample size has been derived for unknown population that is 384. The judgmental sampling technique was used in this research to make this study more inclusive and representatives. Descriptive statistics and inferential statistics (correlation analysis and regression analysis) have been used to analyze the data. It is found that there is strong association between shopping mall purchase behavior and overall consumer attitude. The study found that purpose to visit has impact on shopping mall purchase behavior. The study also found that advertisement has no significant impact on shopping mall purchase behavior.